The epigenetic processes of meiosis in male mice are broadly affected by the widely used herbicide atrazine. (December 2015) - Gely-Pernot, Aurore; Hao, Chunxiang; Becker, Emmanuelle; Stuparevic, Igor; Kervarrec, Christine; Chalmel, Frédéric; Primig, Michael; Jégou, Bernard; Smagulova, Fatima
Abstract Background Environmental factors such as pesticides can cause phenotypic changes in various organisms, including mammals. We studied the effects of the widely used herbicide atrazine (ATZ) on meiosis, a key step of gametogenesis, in male mice. Methods Gene expression pattern was analysed by Gene–Chip array. Genome-wide mapping of H3K4me3 marks distribution was done by ChIP-sequencing of testis tissue using Illumina technologies. RT-qPCR was used to validate differentially expressed genes or differential peaks. Results We demonstrate that exposure to ATZ reduces testosterone levels and the number of spermatozoa in the epididymis and delays meiosis. Using Gene-Chip and ChIP-Seq analysis of H3K4me3 marks, we found that a broad range of cellular functions, including GTPase activity, mitochondrial function and steroid-hormone metabolism, are affected by ATZ. Furthermore, treated mice display enriched histone H3K4me3 marks in regions of strong recombination (double-strand break sites), within very large genes and reduced marks in the pseudoautosomal region of X chromosome. Conclusions Our data demonstrate that atrazine exposure interferes with normal meiosis, which affects spermatozoa production.